Determining the significant factor of Resilient Modulus (MR) Measurement of Bituminous Mixtures by Indirect Tension Test - Firmansyah Firmansyah (Jurnal Teknik Sipil, 2014)
Resilient modulus (MR) is an important property for asphalt concrete design and for mechanistic analysis of pavement response under traffic loading. This study investigates the different factors affecting the MR of hot mix asphalt. A full factorial design of experiment was carried out to investigate four factors. Each factor was studied at two levels. These factors are: number of cyclic loading, loading frequency, Poisson’s ratio, and sample position.Analysis of the factorial experimental design showed that the sample position is the most important factor affecting the resilient modulus. In order to simplify the statistic model, only the main effect are consider inside the model. The power transformation is needed by the model in order to meet IIDN assumption. The model after transformation is:Keywords: resilient modulus, indirect tension, pavement mixture